Algorithm of Inclination Correction for Point Cloud in Dynamic Subsidence Monitoring - Wu, Junhe; Peng, Haiju; Sun, Guibin; Li, Zhi; Huo, Zhihong; Yan, Kewen; Ao, Jianfeng (2020 7th International Conference on Information Science and Control Engineering (ICISCE), 2020)
The stability of an instrument is a key factor in determining the quality of data acquired. During the process of dynamic deformation monitoring in mining areas, due to the impact of highly intensive underground mining practices, some non-uniform subsidence is likely to occur on the ground surface. Such subsidence will lead to relatively large inclination of the instrument within a short time, and consequently cause the automatic inclination compensator to exceed its limits during the scanning process. This is a particular problem encountered when the terrestrial laser scanner (TLS) is used for deformation monitoring in mining areas. This paper mainly analyzes the influence of inclination of the scanner upon precision of point cloud data based on the working principle of the scanner and puts forward an error correction method. First, the inclinations of an instrument at the beginning and at the end of a scanning process are recorded; second, the inclination of the instrument at every moment is determined basing on the relationship between the scanning time and the inclination of the instrument through interpolation, in this way the scanning point coordinates are being corrected. In the end, reasonability and effectiveness of the correction method are verified by means of experiment and comparison between the target control point and the feature planes within the scanning area before and after correction.